Translation and Validation of the Greek Version of the Antipsychotics and Sexual Functioning Questionnaire (ASFQ) - Maria Angelaki, RN, MSc, PhD(c); Petros Galanis, RN, MPH, PhD; Artemis Igoumenou, MD, PhD; Eirini Alexiou, RN, MD, MSc, PhD; Giorgos Alevizopoulos, MD, PhD (Sexual Medicine, 2021)
ABSTRACT: Introduction: Sexual dysfunction in patients with psychoses may be associated with the psychiatric illness itself (negative symptoms, such as apathy, and avolition), comorbid somatic health, psychosocial factors (stigmatization, discrimination), and the use of psychotropic drugs. In Greece, research into the study of antipsychotic-induced sexual dysfunction is not sufficient. Aim: This study was conducted to translate and validate the Greek version of the Antipsychotics and Sexual Functioning Questionnaire (ASFQ) in a sample of patients receiving antipsychotic treatment. Methods: A “forward-backward translation” method was applied. A pilot study was conducted with 15 outpatients with schizophrenia and bipolar disorder under antipsychotics treatment. Patients also completed the “Subjects’ Response to Antipsychotics (SRA)” questionnaire in order to assess the validity of the ASFQ. The ASFQ and the SRA questionnaire were completed twice within 2 weeks. Main outcome measures: Reliability (internal consistency and test-retest) and validity were assessed. Results: The Greek translation of ASFQ was reliable, with excellent internal consistency (Cronbach's a = 0.90 for men and 0.95 for women in both measurements). In addition, the Spearman correlation coefficient was 1 (P< .001) in all Likert-type questions in both assessments. Finally, Spearman correlation coefficients between ASFQ and SRA were moderately positive to strongly positive (between 0.25 and 1) in both assessments, demonstrating moderate to high validity. Conclusions: The Greek version of the ASFQ has proved to be a reliable and valid clinical instrument, hence it can be used in further studies in the Greek population. Angelaki M, Galanis P, Igoumenou A, et al. Translation and Validation of the Greek Version of the Antipsychotics and Sexual Functioning Questionnaire (ASFQ). J Sex Med 2021;9:100334.